Understanding networking technology : concepts, terms, and trends - Norris, Mark (Artech House telecommunications library., 1999)
"With this second edition of Understanding Networking Technology: Concepts, Terms, and Trends you get clear, concise explanations of both common and uncommon computing and telecommunications terminology." "More than just a dictionary of terms, Understanding Networking Technology also helps you make sense of the current state of communications and information technology through sections describing how networking technology has evolved and where it is likely to go in the years ahead. This book takes individual definitions and turns them into comprehensive concepts, explaining their impact and their significance both for today and tomorrow." "It includes hundreds of new terms in such areas as telecommunications protocols, computer network technology, and wireless; and an updated analysis of IT trends, Internet developments, data network growth, and global telecommunications alliances."--Jacket